Mengidentifikasi Tantangan yang Dihadapi oleh Siswa Kelas 3 SDN 171/1 Bajubang Laut dalam Kemampuan Berhitung melalui Observasi - Amanda, Athylla Friska; Sari, Silfiana; Sirait, Lidia Thimora; Sembiring, Armanta (Lembaga Yasin AlSys, 2023)
Learning mathematics has a special purpose in elementary schools so that students can develop numeracy skills as a tool in everyday life, have basic knowledge of mathematics as a provision for further learning in junior high schools, and students can be logical, critical, careful, creative and positive. This research uses a qualitative method with a type of case study research conducted to understand a particular case or situation in depth. The challenge of numeracy ability can have implications for various aspects of a person’s life, be it in daily life, education, and career.